Nutritional analysis of defatted coconut copra meal for use in rabbit (Oryctolagus cuniculus) feeding - Acosta Acosta, Yanixi (2023)
Defatted coconut meal is an agro-industrial by-product that is produced in the municipality of Baracoa, province of Guantánamo, Cuba, in considerable quantities and available for its use as animal feed. The present study evaluated the nutritional quality of defatted coconut flour. A 60 kg sample was taken from one day of production and its composition was determined: dry matter, crude protein, crude fibre, acid detergent fibre, neutral detergent fibre, cellulose, lignin, ashes, minerals (Ca, P, K, Mg) and the fatty acid profile. The results show that the average values for all the nutrients present in defatted coconut meal present an adequate balance of nutrients to be used as raw material in the formulation of diets for animal feed, especially for rabbits. It had a high percentage of crude fibre and crude protein and adequate fatty acid profile.